Two new species of Eugenia (Myrtaceae) from the Atlantic forest of Espírito Santo, Brazil - Giaretta, Augusto; Souza, Marcelo Da Costa; Menezes, Luis Fernando Tavares De; Peixoto, Ariane Luna (Phytotaxa, 2018)
Two Eugenia species are described herein as result of the elaboration of a taxonomic treatment of Myrtaceae for the flora of Restinga vegetation from Espírito Santo, in the Brazilian Atlantic forest. Detailed description, illustration, distribution and evaluation of their IUCN conservation status of Eugenia itaunensis and Eugenia kuekii are presented. Eugenia itaunensis is related to E. copacabanensis from which differs by larger leaves with base obtuse, rounded, cordate or subcordate, 10–18 pairs of secondary veins and greater flowers with calyx lobes in two unequal pairs in size. Eugenia kuekii is morphologically similar to Eugenia widgrenii but differs by leaves with obtuse base, 6–9 pairs of secondary veins, fasciculiform inflorescence with 1–2 pairs of flowers, and yellowish fruits. Eugenia kuekii is also related to Eugenia pruinosa but can be distinguished by its leaves with base obtuse or rounded and calyx lobes larger.